NUTRIENT PROFILE BLACK SOLDIER FLY LARVAE (HERMETIA ILLUCENS): EFFECT OF FEEDING SUBSTRATE AND HARVESTED TIME - Maria Rosalia Weko; Frederius Bao; Maria E. Ega; Hendrika Mia; Klara Susanti Ito Una; Marcelina Viana; Lodovikus Wale; Catootjie Lusje Nalle; Yacob M. Burithnaban; Abner T. Lema; Helda; Asrul (BIOTROPIA, 2023)
The objective of this study was to asses the effect of different feeding substrates (FS), harvesting times (HT), and the interaction between FS and HT on the chemical composition of black soldier fly larvae (BSFL). The experiment used a 4 x 2 factorial arrangement with two main factors, FS (T1, T2, T3, T4), and HT (15-d and 20-d). Thus, there were eight treatment combinations, all together with five replications. The results show that there was no interaction (P>0.05) between FS and HT on dry matter (DM), crude protein (CP), crude lipid (CL), phosphorus (P), gross energy (GE), and amino acid contents. The ash content of BSFL grown on T2 media and harvested on day 15 was higher (P<0.05) than those grown on T2 media and harvested on day 20. The calcium (Ca) content of BSFL grown on all media and harvested on day 20 was higher (P<0.05) than those harvested on day 15. In conclusion, combining fruit wastes and tofu by-products produced BSFL with high CP content but low CL, ash, Ca, and P contents. In addition, BSFL grown on all substrates media and harvested on day 15 had better CP, Ca, and P contents. The dispensable amino acid of BSFLs fed with T3 diets was the best. The lowest body weight gain was produced by feeding a substrate containing a high percentage of rice bran. The findings indicate that the best nutrient composition of BSFL as animal feed would be achieved in early harvest time (15-d) and grown in heterogeneous feeding substrates.